Changes in the South Atlantic Dipole and impacts on the climate of South America under the aspect of climate change - Bier, Anderson Augusto (2023)
Over the past few decades, the South Atlantic Ocean (SAO) has experienced notable changes in its physical characteristics due to human-induced climate change. These changes encompass various aspects such as increased Agulhas leakage, alterations in wind-driven ocean circulation, salinity shifts, and changes in sea surface temperature (SST). In this context, the South Atlantic Dipole (SAD), the main coupled ocean-atmosphere variability mode in the region, may also be subject to modifications. This study aims to examine the historical changes in the SAD (1851-present) and its projections under different future global warming scenarios (2015-2100), utilizing reanalysis data and outputs from the CMIP6 models. The analysis incorporates periods associated with the phases of the Interdecadal Pacific Oscillation (IPO), which are linked to climate variability in the SAO, to evaluate changes in the SAD and the resulting climate impacts on South America during the historical period.Emphasis is placed on understanding the SADs seasonality, particularly its evolution during the austral summer when it exhibits important dynamics with the South American climate. Key findings for the historical period indicate a southward displacement of the entire SAD pattern, consistent with observed oceanic and atmospheric changes attributed to global warming. This shift is accompanied by a transition from a tripole to a dipole pattern of precipitation anomalies over the South American continent during the summer season. Additionally, the SAD demonstrates an alternating relationship with the IPO phases, exhibiting a positive (negative) relationship with Pacific Niño SST anomalies during the IPOs negative (positive) phase. Regarding the representation of the SAD by the best CMIP6 models during the historical period, they generally capture the essential characteristics of this oscillation. These models effectively reproduce features such as the modes characteristics, oscillation period, and seasonal variability. However, they fail to capture the signal associated with the Atlantic Niño (typically linked to the SAD) and the southward shift of the SAD observed in recent decades. In future climate scenarios projected by the CMIP6 models, the main findings concerning the SAD highlight an intensification of SST anomalies, mean sea level pressure (MSLP), and related precipitation. These anomalies are most pronounced under the SSP3-7.0 scenario. Additionally, the different scenarios suggest that the SAD is associated with a dipole pattern of precipitation between North and Southeast South America.